2021
DOI: 10.3390/healthcare9070842
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Conflicts and Self-Reported Insecurity on Maternal Healthcare Utilisation and Children Health Outcomes in the Democratic Republic of Congo (DRC)

Abstract: Background The Democratic Republic of Congo (DRC) has experienced political unrest, civil insecurity, and military disputes, resulting in extreme poverty and a severely impaired health care system. To reduce the morbidity and mortality in women and children by strengthening healthcare, this study aimed at exploring the relationship between self-reported insecurity of mothers and maternal health-seeking behaviours and diseases in children in the DRC. Method Data collected from 8144 mothers and 14,403 children f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…Children from postnatal checkup more likely to early childhood mortality as compared to higher education. This nding is supported by similar studies done in Kenya, Democratic Republic of Congo, and Rwanda [28][29][30][31]. Thus, the regional health bureau, the ministry of health, and policymakers should pay special attention to the above-mentioned regions to reduce early childhood mortality.…”
Section: Discussionsupporting
confidence: 64%
“…Children from postnatal checkup more likely to early childhood mortality as compared to higher education. This nding is supported by similar studies done in Kenya, Democratic Republic of Congo, and Rwanda [28][29][30][31]. Thus, the regional health bureau, the ministry of health, and policymakers should pay special attention to the above-mentioned regions to reduce early childhood mortality.…”
Section: Discussionsupporting
confidence: 64%
“…Other published studies in DRC, Nigeria, and Burundi have found similar evidence, wherein fragile areas not directly affected by conflict may have maternal health indicators that are similar to or worse than those in conflict-affected areas in the same country. Their authors concluded that this phenomenon was likely due to minimal international support and investments in fragile areas [4,47,[61][62][63][64][65] compared with the settings experiencing acute conflict.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that organised violence increases the risk of maternal deaths because of the breakdown or reduction of health infrastructure, constraining women’s and girls’ access to reproductive and maternal health services [ 8 ]; because of structural and secondary factors such as malnutrition, poverty and a lack of clean water [ 9 ]; and sexual and gender-based violence, and other human rights violations [ 10 , 11 ]. We know now that restricted access to family planning and health care initiatives lead to an increase in unwanted pregnancies and unsafe abortions [ 8 , 12 ], with research suggesting that interventions focused on improving access to maternal health can offset the negative effects of war on women’s and girl’s wellbeing [ 13 ] through, for example, increasing the availability of maternal and reproductive health services [ 14 ], clean water and nutrition [ 11 ] and/or peacekeeping operations providing security [ 13 ]. In other words, this body of research has in important ways helped increase recognition of the impact of war on women’s reproductive health and rights by demonstrating 1) that wars impede access to maternal health care; and 2) that this can be offset by targeted interventions focused on increasing access to and availability of health care; contraceptives; and essential nutrients.…”
Section: Women’s Reproductive Health In War and Conflictmentioning
confidence: 99%
“…While some exceptions to this exist [see [ 33 ]], a large proportion of research in global health approach conflict as one phenomenon rather than as a complex and varied political phenomenon with complex and varied gendered effects. For example, studies on maternal health care use in the Democratic Republic of Congo [ 14 , 34 ], Cameroon, Mali, and Nigeria; and Africa [ 35 , 36 ] as well as globally [ 37 , 38 ] take the primary definition of war from the UCDP dataset as given. However, different types of wars have different effects, and it is important to carefully identify and analyse these effects across and within conflicts.…”
Section: Seeing the Full Picturementioning
confidence: 99%